Down-Regulated Expression of Magnesium Transporter Genes Following a High Magnesium Diet Attenuates Sciatic Nerve Crush Injury. Issue 4 (17th April 2018) - Chen, Ying-Ju; Cheng, Fu-Chou; Chen, Chun-Jung; Su, Hong-Lin; Sheu, Meei-Ling; Sheehan, Jason; Pan, Hung-Chuan
Abstract: BACKGROUND: Magnesium supplementation has potential for use in nerve regeneration. The expression of some magnesium transporter genes is reflective of the intracellular magnesium levels. OBJECTIVE: To assess the expression of various magnesium transporter genes as they relate to neurological alterations in a sciatic nerve injury model. METHODS: Sciatic nerve injury was induced in rats, which were then fed either basal or high magnesium diets. Magnesium concentrations and 5 magnesium transporter genes ( SLC41A1, MAGT1, CNNM2, TRPM6, and TRPM7 ) were measured in the tissue samples. RESULTS: The high magnesium diet attenuated cytoskeletal loss in a dose-dependent manner in isolated nerve explants. The high magnesium diet augmented nerve regeneration and led to the restoration of nerve structure, increased S-100, and neurofilaments. This increased regeneration was consistent with the improvement of neurobehavioral and electrophysiological assessment. The denervated muscle morphology was restored with the high magnesium diet, and that was also highly correlated with the increased expression of desmin and acetylcholine receptors in denervated muscle. The plasma magnesium levels were significantly elevated after the animals consumed a high magnesium diet and were reciprocally related to the down-regulation of CNNM2, MagT1, and SCL41A1 in the blood monocytes, nerves, and muscle tissues of the nerve crush injury model. CONCLUSION: The increased plasma magnesium levels after consuming a high magnesium diet were highly correlated with the down-regulation of magnesium transporter genes in monocytes, nerves, and muscle tissues after sciatic nerve crush injury. The study findings suggest that there are beneficial effects of administering magnesium after a nerve injury.